TOURIST PERCEPTION OF THE INTENTION TO VISIT GREEN OPEN SPACE - Lestari, Novi Puji; Pratika, Yeyen (Jurnal Inovasi Ekonomi, 2020)
Tourism is one of the industries that is growing very rapidly in global market. This condition is due to the changes in consumer behavior that makes traveling as a lifestyle and necessity. Green Open Space is one of the tourist destinations that can be used as an attraction as well as an important aspect in the concept of Sustainable Development Goals (SDGs). As one of the tourist destination cities in Indonesia, Batu City has the potential to develop green open space as an alternative tourism destination. The existence of social media in the tourism industry also cannot be ignored given the perceptions that encourage the intention to visit certain tourist destinations. Thus, this study aims to examine the extent to which social media perceptions can influence tourists' intentions to visit green open tourist destinations in Batu. The data collection method in this study uses a questionnaire distributed online and will be obtained using Structural Equation Modeling (SEM).